Assessment of biochemical markers in the early post-burn period for predicting acute kidney injury and mortality in patients with major burn injury: comparison of serum creatinine, serum cystatin-C, plasma and urine neutrophil gelatinase-associated lipocalin - Yang, Hyeong Tae (Crit Care, 2014)
INTRODUCTION: The reported mortality rates range from 28% to 100% in burn patients who develop acute kidney injury (AKI) and from 50% to 100% among such patients treated with renal replacement therapy. Recently, the serum cystatin C and plasma and urine neutrophil gelatinase-associated lipocalin (NGAL) levels have been introduced as early biomarkers for AKI; the levels of these biomarkers are known to increase 24 to 48 hours before the serum creatinine levels increase. In this study, we aimed to estimate the diagnostic utility of the cystatin C and plasma and urine NGAL levels in the early post-burn period as biomarkers for predicting AKI and mortality in patients with major burn injuries. METHODS: From May 2011 to July 2012, 90 consecutive patients with a burn wound area comprising ≥ 20% of the total body surface area (TBSA) were enrolled in this study. Whole blood and urine samples were obtained for measuring the serum creatinine, serum cystatin C, and urine and plasma NGAL levels at 0, 3, 6, 12, 24, and 48 hours after admission. Receiver operating characteristic curve, area under the curve, and multivariate logistic regression analyses were performed to assess the predictive values of these biomarkers for AKI and mortality. RESULTS: In the multivariate logistic regression analysis, all variables, including age, percentage TBSA burned, sex, inhalation injury, and serum creatinine levels, serum cystatin C levels, and plasma and urine NGAL levels were independently associated with AKI development. Moreover, age, sex, percentage TBSA burned, and plasma and urine NGAL levels were independently associated with mortality. However, inhalation injury and the serum creatinine and cystatin C levels were not independently associated with mortality. CONCLUSIONS: Massively burned patients who maintained high plasma and urine NGAL levels until 12 hours after admission were at the risk of developing early AKI and early mortality with burn shock. However, the plasma and urine NGAL levels in the early post-burn period failed to predict late AKI and non-burn shock mortality in this study. Nevertheless, the plasma and urine NGAL levels were independently associated with AKI development and mortality within 48 hours after admission.